2011
DOI: 10.1007/s10337-010-1906-1
|View full text |Cite
|
Sign up to set email alerts
|

LC Assay for a HIV Tablet Containing Emtricitabine, Tenofovir Disoproxil Fumarate and Rilpivirine

Abstract: A liquid chromatographic method with UV detection was developed for the assay of a tablet for HIV (human immunodeficiency virus) treatment containing three active components, which are emtricitabine, tenofovir disoproxil fumarate and rilpivirine. A Hypersil BDS-C18 column was used as stationary phase and the assay was performed with gradient elution using mobile phases containing acetonitrile, 0.2 M potassium dihydrogen phosphate and water. Dimethyl sulfoxide-distilled water (1:1) was used as solvent for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Different separative techniques, such as HPLC–UV [12–17], LC–MS [18,19], and high‐performance thin‐layer chromatography [20], have been introduced for the analysis of antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Different separative techniques, such as HPLC–UV [12–17], LC–MS [18,19], and high‐performance thin‐layer chromatography [20], have been introduced for the analysis of antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…TEN is recovered at 70–80% of the oral dose from urine in the unchanged form (http://www.rxlist.com/viread-drug/clinical-pharmacology.htm) and 6.1% RIL is excreted unchanged in urine (http://www.rxlist.com/edurant-drug/clinical-pharmacology.htm). A literature review reveals some chromatographic methods developed for this drug combination (Pendela et al, ; Prabhakar Reddy, Chandra Teja, Ashraf Sultana, Vijayalakshmi, & Nalluri, ; Pranitha et al, ; Prasad Panigrahy & Kumar Reddy, ). Most of them successfully separate the combinations in about 10–15 min (Khan, Venkateswara, Pulla, Kumar Sudam, & Sujana, ; Pendela et al, ; Prabhakar Reddy et al, ; Pranitha et al, ), although Prasad Panigrahy and Kumar Reddy () achieved it in an 8 min run time using reversed‐phase HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review reveals some chromatographic methods developed for this drug combination (Pendela et al, ; Prabhakar Reddy, Chandra Teja, Ashraf Sultana, Vijayalakshmi, & Nalluri, ; Pranitha et al, ; Prasad Panigrahy & Kumar Reddy, ). Most of them successfully separate the combinations in about 10–15 min (Khan, Venkateswara, Pulla, Kumar Sudam, & Sujana, ; Pendela et al, ; Prabhakar Reddy et al, ; Pranitha et al, ), although Prasad Panigrahy and Kumar Reddy () achieved it in an 8 min run time using reversed‐phase HPLC. Two other HPLC studies were found in the literature by Venkatesan et al Both were published in 2014 (Venkatesan & Kannappan, ; Venkatesan, Kannappan, & Mannemala, ).…”
Section: Introductionmentioning
confidence: 99%